Knowledge Translation in Rehabilitation: A Shared Vision. (July 2017) - Moore, Jennifer L.; Shikako-Thomas, Keiko; Backus, Deborah
Abstract : Purpose: Advances in rehabilitation provide the infrastructure for research and clinical data to improve care and patient outcomes. However, gaps between research and practice are prevalent. Knowledge translation (KT) aims to decrease the gap between research and its clinical use. This special communication summarizes KT-related proceedings from the 2016 IV STEP conference, describes current KT in rehabilitation science, and provides suggestions for its application in clinical care. Summary of Key Points: We propose a vision for rehabilitation clinical practice and research that includes the development, adaptation, and implementation of evidence-based practice recommendations, which will contribute to a learning health care system. A clinical research culture that supports this vision and methods to engage key stakeholders to innovate rehabilitation science and practice are described. Conclusions: Through implementation of this vision, we can lead an evolution in rehabilitation practice to ultimately prevent disabilities, predict better outcomes, exploit plasticity, and promote participation. Abstract : This special communication summarizes knowledge translation, describes the current knowledge translation practices in rehabilitation science, and provides suggestions for its application in clinical care.